Tanggung Jawab Pidana dan Viktimisasi Sekunder dalam Penipuan Segitiga: Analisis Viktimologis dan Hukum Pidana Islam - Ahmad Murtadzo; Maskur Rosyid (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This article examines criminal liability and secondary victimization in triangle fraud through victimology and Islamic criminal law. Using a qualitative socio-legal multiple-case design, it analyzes two fraud cases in Indonesia through in-depth interviews and documentary evidence. The findings show three interrelated forms of secondary victimization: structural victimization caused by weak institutional protection, procedural victimization resulting from asymmetric evidentiary burdens, and social victimization expressed through stigma and victim blaming. The study argues that the core legal problem lies not in the absence of legal norms, but in normative fragmentation, weak attribution of digital evidence, and the lack of a victim oriented enforcement framework. It reconstructs tazir as a flexible normative basis for a victim centered model of criminal liability linking punishment, restitution, and institutional responsibility, and proposes a layered accountability framework involving offenders, digital platforms, and the state